THE INTEGRATION OF INDIAN FOLK ARTS INTO CONTEMPORARY ART: A CULTURAL RENAISSANCE - Yadav, Mantosh; Singh, Raj Kumar; Lal, Mithai; Yadav, J. B.; Chaudhary, Sumit Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The coming together of Indian folk art and modern art marks a big step towards a cultural revival. Folk arts, which has always been a big part of Indian culture, rituals, and spirituality, is now coming back in new ways through the creativity and experiments of modern artists. This connection helps traditional art move beyond its old limits and become relevant again in today’s art world. Artists like Jamini Roy, K.G. Subramanyan, Manjit Bawa, Jagdish Swaminathan, Jayshree Burman, Bhawani Das, and Dr. Lakshman Prasad have been key in this movement. They keep the basic ideas of folk arts alive while adding modern touches, their works shows how traditional art styles can mix with modern approaches, helping Indian folk arts gain more attention at home and abroad. In a world that’s becoming more connected, folk art is changing to fit todays needs and ideas. Now tools and creative methods have made it possible to explore folk traditions in digital formats, mixed media, and other experimental ways. This has created new opportunities more than just keep traditions alive, its also helps them grow and change. This interaction shows a new cultural awakening in Indian art, where old and new ideas work together future for art and keeping India’s artistic traditions alive.